2021
DOI: 10.1002/prca.202100016
|View full text |Cite
|
Sign up to set email alerts
|

Integrating SWATH‐MS proteomics and transcriptome analysis to preliminarily identify three DEGs as biomarkers for proliferative diabetic retinopathy

Abstract: Purpose:We intended to preliminarily find differentially expressed proteins that play crucial roles in proliferative diabetic retinopathy (PDR), and lay the foundation for subsequent further research on the mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the study by Wu et al, FCGR3A was identified as a potential biomarker for patients with PDR. FCGR3A is a member of the FCGR family of plasma proteins 51 . MAPK-related pathways are currently a hot topic in DR research.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Wu et al, FCGR3A was identified as a potential biomarker for patients with PDR. FCGR3A is a member of the FCGR family of plasma proteins 51 . MAPK-related pathways are currently a hot topic in DR research.…”
Section: Discussionmentioning
confidence: 99%
“…The early detection of PDR is a challenge that has not yet been overcome in clinical work, and this is due to there being a lack of a simple, rapid, and specific molecular markers to detect the progression of PDR. In the plasma of PDR patients, a total of 23 upregulated and 13 downregulated proteins were found, with FCGR3A, DPEP2, and ADGRF5 identified as potential protein markers in the plasma [ 93 ]. Wang et al [ 85 ] used RP-HPLC and ESI-MS/MS to detect 96 differentially expressed proteins, 37 upregulated proteins, and 59 downregulated proteins in the vitreous of PDR patients.…”
Section: Application Of Proteomics In Optic Nerve Injury Diseasesmentioning
confidence: 99%
“…Previous reports suggest that DPEP2 acts as an inflammatory regulator of macrophages and may have a protective effect against CVB3-induced viral myocarditis [ 12 ]. DPEP2 has also been identified as a potential biomarker for diabetic retinopathy [ 13 ]. In respiratory diseases, DPEP2 has been implicated in chronic rhinitis, sinusitis, and asthma [ 14 ].…”
Section: Introductionmentioning
confidence: 99%